Analysis of The Influence of Land Use on Water Quality Pollution in The River Basin (DAS) Kali Pelayaran, Sidoarjo - Diah Retno Jayantri; Nieke Karnaningrum (Jurnal Serambi Engineering, 2024)
Most rivers in Indonesia experience pollution due to waste disposal activities that are often uncontrolled in terms of both quantity and quality. Increased domestic activities, infrastructure development and land use around the watershed have had a significant impact on water quality in Pelayaran River. Pelayaran River with a length of 21 km is the source of raw material for drinking water processed by Taman Tirta Water Treatment Plant (IPA) in Sidoarjo Regency. This study aims to assess the condition of pollutant load in Pelayaran River, Sidoarjo. The research method used is by testing the status of river water quality using the pollution index, followed by simulating river water quality using Qual2kw with 3 scenarios, and calculating the capacity of the pollutant load. the water quality parameters analyzed are COD, BOD, TSS, and Total Nitrogen parameters. from the results of this study, it can be seen that the quality status of Kali Pelayaran and the capacity of the pollutant load. it is hoped that this research will be able to provide policy decisions in making water quality pollution control strategies